The Development and Implementation of a Simulated Patient Resource for Teaching and Assessment in Optometry Low Vision Rehabilitation - Karas M; Lucas N; Ryan B (Clinical Optometry, 2025)
Marek Karas, Natalie Lucas, Barbara Ryan School of Optometry and Vision Sciences, Cardiff University, Cardiff, UKCorrespondence: Marek Karas, School of Optometry and Vision Sciences, Cardiff University, Cardiff, UK, Tel +44 (0)29 2087 6316, Email karasm@cardiff.ac.ukPurpose: To report on the development, evaluation, and acceptability of a simulated patient resource designed for teaching and assessment in low vision rehabilitation. The findings aim to inform possible future integration of this method into optometric education.Methods: In response to COVID-19 restrictions, a simulated patient resource was developed to allow students undertaking the practical elements of postgraduate modules in low vision practice at Cardiff University to complete their training. Using a mixed methods case study approach, the evaluation examined perspectives from students, assessors, and simulated patients, to establish if there was a consensus of opinion on its use. The study did not seek to demonstrate educational impact or validate SiP against existing methods.Results: Five assessors, five simulated patients and seven students completed evaluations. Both assessors and students broadly accepted the method for both teaching and assessment, with mean scores across all groups ranging from 7.3 to 9.6 on a 1– 10 scale (where 1 indicated very poor acceptance and 10 excellent acceptance). The discussion and establishing magnification elements of the encounter were the least well accepted. Simulated patients found the level of preparation for the role adequate. There were no significant differences between Likert scores between assessors and students in both the teaching and assessment sessions. Thematic analysis of free text comments showed in the main positive responses, with all groups highlighting the benefits of detailed scenarios and pre-session training. The method was acceptable to the professional governing and accrediting body, the College of Optometrists.Conclusion: Implementing a guideline-compliant simulated patient resource for high-stakes assessment requires significant time and resources. Our single cohort analysis indicates broad acceptance amongst assessors and students. Further research is needed to evaluate its educational impact across a wider range of scenarios and competencies while also further assessing its validity. Though simulated patients offer a viable alternative for teaching and assessing low vision practice, real patient encounters remain preferable.Plain Language Summary: Simulation-based education in healthcare replicates real-life scenarios for teaching purposes. One method used is the simulated patient; these are individuals trained to portray patients with specific health conditions. This approach allows healthcare professionals to develop, practice, and be assessed on their clinical consultation skills.During the COVID-19 pandemic, we developed a program at Cardiff University to train and use simulated patients, enabling eye care practitioners to complete their training in low vision practice. This paper outlines how we used accepted guidelines to design this resource and analyses feedback from students, simulated patients, and teaching staff involved in using it.Our experiences taught us that developing and implementing such a simulated patient resource requires significant time and resources. Even though feedback suggested that the method is mostly acceptable to both assessors and students, we have concluded that having access to a readily available pool of real patients is the more credible option for teaching and assessing this accredited level of low vision practice. However, in the absence of real patients, the use of simulated patients is a viable option for teaching and assessing low vision practice, provided the resource is carefully planned and implemented.We feel that more research is needed to explore how this method could be used effectively and more widely in teaching and assessing other optometric skills.Keywords: simulated patients, low vision, low vision rehabilitation, optometry, post graduate teaching, simulation-based learning